ANALISIS FRAMING POLRI PADA PENANGANAN DEMONSTRASI UU CIPTA KERJA DI KOMPAS.COM DAN DETIK.COM - Tiara Febriani; Lusia Handayani; Vinta Sevilla (Jurnal Pustaka Komunikasi, 2022)
UU Cipta Kerja experienced pros and cons after it was passed on October 4, 2020. Therefore, various community groups hold demonstrations throughout October 2020. Polri has duties and obligations in handling and securing demonstrations. This incident attracted a lot of attention from Indonesian citizen, therefore online news portals such as kompas.com and detik.com raised this news. This study aims to find out how detik.com and kompas.com frame the police's handling demonstrations against the job creation law through Robert Entman's framing model and construct the reality of the news. This study uses qualitative descriptive approach with constructivist paradigm and uses framing analysis method. Results showed that kompas.com considered the Police to have not handled demonstrations according to their duties and obligations, while detik.com considered the Police to have handled demonstrations well. The construction of the reality of kompas.com is that the Police aggressive and repressive actions and tend to be pro to masses, while detik.com constructs that the Police perform well and corner the anarcho groups who are rioting. Differences in reality construction occur due differences in media ideology, where kompas.com has social democratic ideology that has  humanist approach, then detik.com has nationalist ideology that tends to side with government officials.